Government Policy and Public Relations Contribution to the Public Crisis (Covid-19) - Adrian Kede; Muh. Iqbal Sultan; Sudirman Karnay (Research Synergy Foundation, 2021)
Government is an institution that has the authority to create populist policies in dealing with the impact of the Covid-19 pandemic on society. Furthermore, Public Relations is an important part that can communicate government policies to the public. This study aims to analyze government policies and public relations to the Covid-19 public crisis in Banggai district. The research method used is descriptive qualitative with a case study approach. This study uses the purposive sampling technique; the informants arethe Regent of Banggai and the head of the Covid-19 Task Force, and the Head of Public Relations. Data collection techniques used through observation, interviews, documentation, and data analysis techniques used are the interactive model of Miles and Huberman in data collection, data reduction, data presentation, and concluding. The results of this study describe local government policies in the form of quick responses (quick win), health management, handling of economic impacts, and provision of social safety nets, as well as the contribution of Public Relations in the form of policy campaigning through print media, electronic media, social media (Facebook, Instagram, WhatsApp), banners and conventional communication patterns (appeals through places of worship and BPU).